Sintomas schneiderianos como fatores de remissão de pacientes em primeiro episódio de psicose sem tratamento prévio - Tasso, Brazilio de Carvalho [UNIFESP] (2017)
Schizophrenia is a psychotic disorder that usually features progressive evolution and debilitating outcome. It is a heterogeneous disease, in regard to both clinical presentation and outcome. The First Rank Symptoms (FRS) for Schizophrenia, proposed by German psychiatrist Kurt Schneider in 1959, were important to define current diagnosis criteria, but their relevance for response to treatment is yet to be confirmed. The present study intends to evaluate if FRS are indeed capable of predict remission in first episode psychoses drug naive patients. Method: cohort study with 189 patients experiencing their first episode of psychosis. Those patients had never been subjected to any previous treatment with anti psychotic agents. They completed a social-demographic inquiry and clinical scales (PANSS, SCID, GAF, and CGI). A FRS check list was designed. Then, they were medicated with the antipsychotic agent risperidone for two months. After that, they were again subjected to the same assessment scales. Results: there is positive statistic correlation between experiencing at least one of the FRS and receiving the diagnosis of schizophrenia ( p<0,001). There was no correlation between number of FRS and remission. When FRS were individually assessed, “voices making observations about the subject” had positive correlation with remission, considering the whole sample controlled for sex and age(p<0,05). Discussion: data suggest that the FRS are very prevalent (77%), and patients who display them are more likely to receive the diagnosis of schizophrenia. There seems to be no clear correlation between FRS and remission. The role of the FRS voices making observations about the subject need further study in order to assess its clinical application.